The Relationship Between Students’ Reading Motivation and the Success to Comprehend the English Texts - Fauzi, Iwan; Saman, Tampung N; Zannah, Nurul; Octaviani, Shellina; Winey, Brigita Girlani (Journal of English Teaching and Learning Issues, 2022)
Reading is one of the main skills that must be possessed by students in order to be successful in learning English as a foreign language. Meanwhile, motivation is very much needed in English learning because motivation is one of the determinant factors of student to succeed. The relationship of reading and motivation is two coin-sides that encourage anyone to read or not to read. The aim of making this study is to determine the relationship between students' reading motivation and reading comprehension. This study takes the setting of students who learn English as a foreign language at a state university in Palangka Raya--Indonesia during one month and half by selecting 36 college students with an age range between 19-21 years covered by 22 females and 14 males. This study used a correlational research design. The result shows that there is a positive correlation between students’ reading motivation and their reading comprehension which means the more motivated students in reading the more increased their comprehension in reading the texts.